2009
DOI: 10.1111/j.1863-2378.2008.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection withToxocara catiin BALB/c Mice, Migratory Behaviour and Pathological Changes

Abstract: Experimental inoculations of 1000 Toxocara cati larval eggs were carried out in 18 BALB/c mice. The T. cati eggs used for inoculation were collected from the faeces of naturally infected cats. Euthanasia was performed on two mice on days 1, 2, 3, 4, 5, 6, 14, 21 and 28 post-inoculation (p.i.). Tissue samples were taken for digestion and histopathology. Larvae were recovered from all infected mice and the average of all larvae recovered was 28.3% (95%; CI: 14.1-42.4). Maximum number was obtained from liver on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 38 publications
(53 reference statements)
3
27
0
1
Order By: Relevance
“…In agreement with Kayes (2006), we confirmed that both visceral and ocular toxocarosis can develop during primary infection by massive parasite infectious dose, though similar clinical picture can develop also during reinfections. The time course of T. cati infections is in agreement with data of Cardillo et al (2009), Olson (1976, Prokopič and Figallová (1982), and Ghafoor et al (1984). We showed that the larvae can invade the brain and eye also during early phase of primary infection.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with Kayes (2006), we confirmed that both visceral and ocular toxocarosis can develop during primary infection by massive parasite infectious dose, though similar clinical picture can develop also during reinfections. The time course of T. cati infections is in agreement with data of Cardillo et al (2009), Olson (1976, Prokopič and Figallová (1982), and Ghafoor et al (1984). We showed that the larvae can invade the brain and eye also during early phase of primary infection.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, earlier activation of OPCs in T. cati infection might reduce or prevent histologically and clinically apparent signs of demyelination and therefore may explain why these animals developed clinical symptoms and histologically apparent signs of demyelination much later than T. canis-infected individuals. On the other hand, this histological lack of demyelination and clinical symptoms may simply be due to lower numbers of T. cati larvae reaching the brain as they accumulate in muscle tissue mostly (Cardillo et al 2009;Janecek et al 2014), which likely results in minor neuropathological effects compared to T. canis. Additionally, other genes such as Mag are solely affected in T. canis-infected mice in both cerebra and cerebella.…”
Section: Discussionmentioning
confidence: 90%
“…In cerebella and cerebra of T. cati-infected mice, Cnp is downregulated later, 150 dpi. Since T. cati larvae predominantly accumulate in muscle tissue while only a minor proportion migrates to the brain (Cardillo et al 2009;Janecek et al 2014), it can be expected that clinical symptoms, histological changes and signs of demyelination appear later in the course of infection. Essentially, fewer larvae require more time to accomplish a clinically apparent degree of parenchymal brain damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Toxocara eggs in the present study have not been distinguished morphologically, we do not know how many of the Toxocara eggs found coproscopically were actually only contaminants from ingested cat faeces. However, it deserves special attention as there is no difference in the zoonotic potential of T. canis and T. cati (Cardillo et al 2009). …”
Section: Prevalence Of Endoparasites In Dogsmentioning
confidence: 97%